URBAN TRANSFORMATION PROCESS IN TURKEY, CASE STUDY: AYAZMA - TEPEUSTU APPLICATION PROJECT - Denli, Hayri Hakan; Hun, Oyku; Cetin, Seda; Bitik, Esin (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
Urban transformation projects in which different aspects are put on the agenda are implemented to restore the quality of urban life in the depressed areas of cities, loosing their functions and intensity of use in the past, in terms of economic, physical and social aspects. During the application process of the urban transformation phenomenon which has a multidimensional content, a project produced by considering humans, the natural structure, and the historical development of the locality should be evaluated by taking into account its identity, innovator approach, economic, social, and ecological constituents. It is a fact that a model without participants cannot be carried out. In the urban transformation process, it is important not only to take role as decision makers and applicators such as public governments, private sectors and professionals but also to ensure the participation of the users to result with success. In this study, the urban transformation projects in our country are investigated, especially the positive and negative sides of these projects are researched, and tried to make some proposes with a case study Kucukcekmece Ayazma - Tepeustu urban transformation implementing project.
Keywords: Urban transformation; Ayazma - Tepeustu urban transformation project; urban transformation in Turkey; Environmental Sciences & Ecology